2021
DOI: 10.1021/acs.est.1c01919
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Hydrocarbon Surfactant on the Retention and Transport of Perfluorooctanoic Acid in Saturated and Unsaturated Porous Media

Abstract: The transport and retention behavior of perfluorooctanoic acid (PFOA) in the presence of a hydrocarbon surfactant under saturated and unsaturated conditions was investigated. Miscible-displacement transport experiments were conducted at different PFOA and sodium dodecyl sulfate (SDS) input ratios to determine the impact of SDS on PFOA adsorption at solid–water and air–water interfaces. A numerical flow and transport model was employed to simulate the experiments. The PFOA breakthrough curves for unsaturated co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 53 publications
(107 reference statements)
2
26
0
Order By: Relevance
“…Several of the CD method studies also indicate some degree of solid-phase partitioning. ,,,,, The competition between solid-phase sorption and air–water interfacial sorption is another possible reason why drainage-based studies consistently observe lower K ia values than equilibrium values predicted by the Freundlich model. Competitive sorption will need to be considered for field sites, where the presence of organic matter, , nonaqueous phase liquids (NAPLs), , solid sorbents, and competing sorbates ,, could cause a reduction in the equilibrium partitioning of PFAAs to the air–water interface.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the CD method studies also indicate some degree of solid-phase partitioning. ,,,,, The competition between solid-phase sorption and air–water interfacial sorption is another possible reason why drainage-based studies consistently observe lower K ia values than equilibrium values predicted by the Freundlich model. Competitive sorption will need to be considered for field sites, where the presence of organic matter, , nonaqueous phase liquids (NAPLs), , solid sorbents, and competing sorbates ,, could cause a reduction in the equilibrium partitioning of PFAAs to the air–water interface.…”
Section: Discussionmentioning
confidence: 99%
“…42,47−49 PFAS retention at air− water interfaces at these higher concentrations may be less than at lower concentrations, depending on the sensitivity of the air−water partitioning coefficient to PFAS concentration and its applicability at lower concentrations. 24,27,29 Each experiment consisted of five steps (illustrated in Figure S1). First, the nonreactive tracer was pumped through the water-saturated sand pack.…”
Section: Methodsmentioning
confidence: 99%
“…PFAS partition to air–water interfaces because of their surfactant properties. ,, The extent of partitioning is proportional to the air–water interfacial area, which generally increases with decreasing water saturation. , Previous studies conducted using PFOS and PFOA over a range of water saturations have shown that 50–80% of total retention in sand can be attributed to the air–water interface. , Air–water interfacial adsorption has also been shown to depend on ionic strength of the background solution, chain length, functional headgroup, and PFAS concentration. Although some studies have used batch experiments or surface tension measurements to investigate air–water adsorption, recent studies have focused on transport experiments. ,, These transport experiments have demonstrated less retention than predicted using a Freundlich isotherm (rather than a Langmuir isotherm), particularly for PFOA, and that the discrepancy between predicted and measured retention increases with decreasing PFAS concentration …”
Section: Introductionmentioning
confidence: 99%
“…SDS refers to sodium dodecyl sulfate. The multi‐process mass‐transfer models, including Brusseau 2020 (a–b) (Brusseau, 2020), Brusseau 2021 (c–d) (Brusseau et al., 2021) (Guo et al., 2020), and (e–f) (Ji et al., 2021) can describe the transport behaviors of PFAS under saturated and saturated porous media. Copyrights: 2020 Elsevier, 2021 Elsevier, and 2021 American Chemical Society (reproduction with permission).…”
Section: Modeling Pfas Transport In Subsurface Environmentsmentioning
confidence: 99%